Legitimacy and constitutional stability as challenges for Poland's accession to the European Union (Contemporary Central & East European Law, 2002)
This article is about the agreement of politicians and citizens of Poland for access to EU. Polish Constitution from 1997  was written by experts and accepted by a slim majority in referendum. It made a lot of controversies and similar controversies were made by the Polish Government which tried to make Poland part of EU Membership.The paper is an updated and shortened version of a report presented at the international conference The politics of enlargement in Central and Eastern Europe: Changing rules and institutions organised by the Leiden University and Academia Istropolitana Nova, Bratislava (September 2000).